Associations between Physical Activity and Mental Health in Iranian Adolescents during the COVID-19 Pandemic: An Accelerometer-Based Study - Saeed Ghorbani (MDPI AG, 2021)
Using self-reported questionnaires, several studies found that social isolation during the COVID-19 pandemic has significantly changed the level of physical activity (PA) in children and adolescents. Since the objectivity of self-reported PA is limited in several ways, we used modern accelerometers in this study to assess the PA levels of male and female adolescents during the pandemic-related lockdown. Moreover, the association of PA with mental health of the adolescents were analyzed. A total of 136 students (76 girls, mean age of 16.28 ± 0.97 years) from various schools in Iran wore the accelerometer (ActiGraph GT3X-BT) for seven consecutive days. Mental health was measured through the Depression, Anxiety, Stress Scale-21 of Lovibond and Lovibond (1995). Descriptive statistics and independent t-tests were used to analyze the PA levels of male and female students, and linear regressions were computed to examine whether PA predicts mental health status. On average, the daily time spent in moderate-to-vigorous PA (MVPA) was 18.47 min, which is clearly below the WHO guideline of at least 60 min of MVPA per day. Only 4% of adolescents showed MVPA for more than 30 min per day. Male students were significantly more active than their female peers (p = 0.015). As expected, MVPA was negatively associated with mental health issues such as depression, anxiety, and stress. However, the majority of adolescents reported symptoms of mild-to-moderate mental health disorders. These results emphasize the need for targeted strategies and offerings geared to young people’s needs and preferences to promote an adequate level of PA and good mental health during and after the ongoing pandemic.